Pengaruh pemberian ZPT terhadap pertumbuhan beberapa jenis setek tanaman Puring (Cadiaeum variegatum L.) - Theresia Tan; Linda Ernawati Lindongi; Yohanes Sriyadi Budiyanto; Feni Tresia Merasi (Agrotek, 2022)
This study aimed to determine the effect of growth regulators addition on the growth of cuttings from several types of croton plants. This study was designed using a factorial Randomized Block Design (RBD) consisting of 2 factors. The first factor is the type of puring which consists of golok kuning croton (P1), emping croton (P2), raja croton (P3), jet croton (P4), emping croton (P5), cokwe croton (P6). The second factor is without growth regulators (Zo), Rootone-F (Z1) and coconut water (Z2). The results showed that the interaction between PGR and the type of croton gave an insignificant effect on the growth of croton cuttings on all observed variables. Croton type showed a significant effect on all variables observed in cuttings growth except for the percentage of cuttings sprouting. The best cutting growth was shown by golok kuning croton.